Analysis of The Mechanical Properties of Concrete Based on Fly Ash and Palm Oil Clinkers - L Opirina; Azwanda Azwanda; R Febrianto (International Journal of Engineering, Science and Information Technology, 2021)
Concrete is the result of a mixture of cement, aggregate and water. Under certain conditions, the concrete mixture can be added with additives and admixture to get the concrete as needed. Cement is the most important material in the manufacture of conventional concrete. When cement is produced, the same amount of CO2 will also be generated as a side effect and pollute the atmosphere. Fly ash as an alternative to cement will be introduced as an alternative concrete material to reduce the use of cement in the concrete mix. In addition to the use of charcoal fly ash as a partial substitute for cement, this study also uses palm oil clinkers as a substitute for fine aggregate as much as 20%. This replacement material is an industrial waste which has the main content of silica and alumina which is similar to the main material for forming concrete. In addition, the use of these two materials also aims to reduce the exploration of the use of natural materials. This research introduces 3 kinds of concrete composition. The grouping is based on the ratio of fly ash and cement used, namely (60%:40%), (70%:30%) and (80%:20%). The test object used is a concrete cylinder with a diameter of 150 mm and a height of 300 mm. Tests were carried out at the age of 28 days of concrete. The compressive strength test showed that the best concrete was produced from the combination of the addition of 60% fly ash of coal aged 28 days, which was 4.21 MPa.